IMPLEMENTASI MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR PPKN DAN MENUMBUHKAN NILAI KARAKTER SISWA DI KELAS VIII SMP NEGERI 1 TORGAMBA - Budi Winata Hasibuan (JURNAL TEMATIK, 2015)
This study aims to improve student learning outcomes and student character Civics value by applying the model of problem-based learning in class VIII-1 SMP 1 Torgamba. This research is a classroom action research with the research subjects are students in the class VIII-1, amounting to 32 people. The object of this research problem-based learning model application in improving student learning outcomes and student character. Based on the results obtained by the first and second cycles can be concluded that the implementation of problem based learning in class VIII-1 to improve student learning outcomes and student scores in the category of successful characters